FoxO Proteins in the Nervous System. (10th June 2015) - Maiese, Kenneth
Abstract : Acute as well as chronic disorders of the nervous system lead to significant morbidity and mortality for millions of individuals globally. Given the ability to govern stem cell proliferation and differentiated cell survival, mammalian forkhead transcription factors of the forkhead box class O (FoxO) are increasingly being identified as potential targets for disorders of the nervous system, such as Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, and auditory neuronal disease. FoxO proteins are present throughout the body, but they are selectively expressed in the nervous system and have diverse biological functions. The forkhead O class transcription factors interface with an array of signal transduction pathways that include protein kinase B (Akt), serum- and glucocorticoid-inducible protein kinase (SgK), I κ B kinase (IKK), silent mating type information regulation 2 homolog 1 ( S. cerevisiae ) (SIRT1), growth factors, and Wnt signaling that can determine the activity and integrity of FoxO proteins. Ultimately, there exists a complex interplay between FoxO proteins and their signal transduction pathways that can significantly impact programmed cell death pathways of apoptosis and autophagy as well as the development of clinical strategies for the treatment of neurodegenerative disorders.